How do they grow out of their cancer experience? Korean adolescent and young adult cancer survivors' stories. Issue 8 (17th November 2021) - Yi, Jaehee; Kim, Min Ah; Akter, Jesmin
ABSTRACT: Objectives: Cancer experiences can bring positive as well as negative impacts. The current literature, however, focuses mainly on the negative impacts. This qualitative study examines Korean childhood cancer survivors' post-traumatic growth, which concerns how they respond positively to the cancer experience and how they change as a result of their experience. Design: In-person or telephone interviews were conducted with 31 adolescent and young adult survivors of childhood cancer post-treatment who were living in Korea. Results: Thematic analysis found that childhood cancer survivors experienced growth by feeling gratitude (being content with the present, making comparisons with worse situations), engaging in self-affirmation ('I am strong'; 'My example can help others'; 'I am ready for new challenges'), deepening faith (communicating with God, trusting God's direction), and finding the social meaning of cancer (becoming a self-advocate, mapping out a career path). Conclusions: The study findings can be used by psychosocial care professionals to support Korean cancer survivors to recognize post-traumatic growth and, thus, achieve improved well-being.